Pelatihan Penulisan Artikel Ilmiah Bidang Farmasi Based On Research Mahasiswa DIII-Farmasi Universitas Muhammadiyah Palangkaraya Pada Jurnal Nasional Terakreditasi - Ardhany, Syahrida Dian; Novaryatiin, Susi; Saputra, Rizky Nasrullah Fadlani; Nugroho, Dimas Prasetyo Aji; Izzaty, Nur; Ifmayanti, Elsa (Majalah Cendekia Mengabdi, 2023)
Introduction: The importance of scientific writing is to introduce literature activities to students. Based on field observations, it can be stated that the ability to write scientific manuscript for students, especially those intended for publication, is still very poor. Objective: This activity aims to increase the understanding of DIII pharmacy UMPR students about the process of scientific manuscript published based on research in accredited national journals (SINTA 1-6). Methods: The method of carrying out this activity is coaching in writing of scientific manuscript in accredited national journals by providing theory related to the process of making scientific manuscript until published. Results: This community service activity was assessed based on the results of the pretest and post-test statistics using IBM SPSS ver 26. The results showed scores of post-test 2 participants decreased, 21 participants increased, and 7 participants had the same scores both post-test and pre-test. The wilcoxon test result was obtained P= 0.000 (P<0.05). Conclusions: Based on this community service activity, it can be concluded that there was an effect a coaching for writing scientific manuscript based on statistics test (P= 0.000).